Pilot Scale Processing of Red Flesh Guava RTS Beverage - S Bhuvaneswari; R B Tiwari (Journal of Horticultural Sciences, 2007)
Pilot scale studies on production of ready-to-serve (RTS) beverage from red flesh guava were done using 100 kg of the fruit. Pulp yield was more (73.68 %) in lye peeling than in hand peeling (58.68 %). RTS beverage was prepared by mixing fruit pulp with syrup to an optimum level of acidity and sugar, as standardized on a laboratory scale. Blending RTS beverage by using colloidal mill improved the colour, consistency and overall quality. From 100 kg of red flesh guava, 247 litres of RTS beverage could be obtained. The cost:benefit ratio and value addition from this process were worked out at 1.79 and Rs. 5.45/kg of fruit, respectively.